2007
DOI: 10.32725/jab.2007.019
|View full text |Cite
|
Sign up to set email alerts
|

Chondrogenic differentiation of human bone marrow and adipose tissue-derived mesenchymal stem cells

Abstract: Congenital abnormalities, various diseases and injuries may result in the degeneration of articular cartilage. Recently, stem cell therapy has offered new treatment possibilities for this condition. The aim of our study was to verify the chondrogenic differentiation potential of human bone marrow mesenchymal stem cells (BMSCs) and adipose tissue-derived mesenchymal stem cells (AMSCs) in vitro in the presence or absence of transforming growth factor beta (TGF-β1). Human BMSCs and AMSCs from healthy donors were … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
13
0
2

Year Published

2012
2012
2019
2019

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(16 citation statements)
references
References 37 publications
1
13
0
2
Order By: Relevance
“…hADSCs are more readily available than bone marrow‐derived MSCs, for instance, obtained by aspiration of bone marrow cells in a procedure that has risks and complications. It has been proven that human adipose‐derived mesenchymal stromal cells (hADSCs) are adhesive, have a fibroblast‐like morphology, express multiple CD marker antigens satisfying MSCs phenotype and possess multilineage potential to differentiate in mesenchymal lineages . Several previous studies have shown that hADSCs undergo chondrogenesis and deposit a cartilage‐specific matrix in pellet cultures and in a variety of natural and synthetic scaffold materials in the presence of the appropriate growth factors …”
Section: Introductionmentioning
confidence: 99%
“…hADSCs are more readily available than bone marrow‐derived MSCs, for instance, obtained by aspiration of bone marrow cells in a procedure that has risks and complications. It has been proven that human adipose‐derived mesenchymal stromal cells (hADSCs) are adhesive, have a fibroblast‐like morphology, express multiple CD marker antigens satisfying MSCs phenotype and possess multilineage potential to differentiate in mesenchymal lineages . Several previous studies have shown that hADSCs undergo chondrogenesis and deposit a cartilage‐specific matrix in pellet cultures and in a variety of natural and synthetic scaffold materials in the presence of the appropriate growth factors …”
Section: Introductionmentioning
confidence: 99%
“…That being said, when analyzing respective MSC content, there is evidence that MSCs from adipose sources proliferate more rapidly in culture, are less susceptible to senescence secondary to culture expansion, and yield a higher MSC concentration per unit volume of tissue [2]. We question, however, whether these culture‐based findings translate to regenerative potential, as multiple studies have indicated bone marrow–derived stem cell products possess greater chondrogenic capacity than adipose‐derived ones [3‐5]. Additionally, the very source cited by our opponents in support of ADSCs over BMAC also states that “it should be noted that the in vitro differentiation potential of MSCs does not necessarily predict or correlate with their in vivo differentiation capacity.… If paracrine factors are implicated in the therapeutic effects of these MSCs, there would be little difference between the 2 cell types [2].”…”
Section: Case Scenariomentioning
confidence: 99%
“…While there is confl icting evidence regarding the chondrogenic differentiation superiority of AMSCs compared to BMMSCs (Lee et al 2004;Im et al 2005;Danišovič et al 2007), the potential of AMSCs to elicit a T-cell response in early passages along with a potential to form cancer-like cells over long culture durations hinder the potential of AMSCs to be used in the clinic for cartilage repair (Puissant et al 2005;McIntosh et al 2006;Peroni et al 2008). …”
Section: Adipose Derived Stem Cells (Amscs) For Cartilage Repairmentioning
confidence: 99%